Theories of small groups : interdisciplinary perspectives - Poole, Marshall Scott, 1951-; Hollingshead, Andrea B. (Sage, 2005)
"Theories of Small Groups: Interdisciplinary Perspectives brings together the threads that unify the field of group research. The book is designed to define and describe theoretical perspectives on groups and to highlight select research findings within those perspectives. In this text, editors Marshall Scott Poole and Andrea B. Hollingshead capitalize on the theoretical advances made during the last fifty years by integrating models and theories of small groups into a set of nine general theoretical perspectives. Theories of Small Groups is the first book to assess, synthesize, integrate, and evaluate the body of theory and research on small groups across disciplinary boundaries." "Theories of Small Groups can be used by researchers and in graduate courses that will train the next generation of group scholars. It is an excellent supplementary textbook for graduate courses on small groups in many disciplines, including Communication, Psychology, Management, Sociology, Political Science, and Education."--Jacket.